Pengaruh Ekstrak Virgin Olive Oil (EVOO) terhadap Ekspresi Nuclear Factor Kappa Beta (NF-kB) pada Tikus Rattus Novergicus Model Preeklamsia - Retnaningrum, Dwi Norma; Rahmawati, Wenny (Jurnal Ners, 2025)
Preeclampsia is a serious condition that threatens the safety of pregnant women worldwide. This condition causes high blood pressure and organ dysfunction in pregnant women who have reached 20 weeks of gestation. One of the main causes of preeclampsia is cellular damage due to free radicals and inflammation in the body, which can be detected through increased levels of NF-kB protein that triggers inflammation. This research examines the benefits of extra virgin olive oil (EVOO) in addressing this problem. Extra virgin olive oil was chosen because it is rich in polyphenol compounds that can fight free radicals and reduce inflammation. The researchers wanted to prove whether giving extra virgin olive oil could reduce NF-kB protein levels in the placenta of experimental rats experiencing preeclampsia-like conditions. The study was conducted by comparing five groups of pregnant rats: a group without treatment, a group induced to develop preeclampsia, and three groups given extra virgin olive oil at different doses (0.5 mL, 1 mL, and 2 mL per day). The research results showed that extra virgin olive oil administration was proven effective in reducing NF-kB protein levels in rat placenta, and the higher the dose given, the better the results. These findings provide hope that extra virgin olive oil can be a safe and natural complementary treatment option to help reduce inflammation in pregnant women with preeclampsia. This research paves the way for utilizing natural ingredients in preventing and managing preeclampsia, which ultimately can help save the lives of mothers and babies.